P38α‐MAPK‐deficient myeloid cells ameliorate symptoms and pathology of APP‐transgenic Alzheimer's disease mice. Issue 8 (31st July 2022) - Luo, Qinghua; Schnöder, Laura; Hao, Wenlin; Litzenburger, Kathrin; Decker, Yann; Tomic, Inge; Menger, Michael D.; Liu, Yang; Fassbender, Klaus
Abstract: Alzheimer's disease (AD), the most common cause of dementia in the elderly, is pathologically characterized by extracellular deposition of amyloid‐β peptides (Aβ) and microglia‐dominated inflammatory activation in the brain. p38α‐MAPK is activated in both neurons and microglia. How p38α‐MAPK in microglia contributes to AD pathogenesis remains unclear. In this study, we conditionally knocked out p38α‐MAPK in all myeloid cells or specifically in microglia of APP‐transgenic mice, and examined animals for AD‐associated pathologies (i.e., cognitive deficits, Aβ pathology, and neuroinflammation) and individual microglia for their inflammatory activation and Aβ internalization at different disease stages (e.g., at 4 and 9 months of age). Our experiments showed that p38α‐MAPK‐deficient myeloid cells were more effective than p38α‐MAPK‐deficient microglia in reducing cerebral Aβ and neuronal impairment in APP‐transgenic mice. Deficiency of p38α‐MAPK in myeloid cells inhibited inflammatory activation of individual microglia at 4 months but enhanced it at 9 months. Inflammatory activation promoted microglial internalization of Aβ. Interestingly, p38α‐MAPK‐deficient myeloid cells reduced IL‐17a‐expressing CD4‐positive lymphocytes in 9 but not 4‐month‐old APP‐transgenic mice. By cross‐breeding APP‐transgenic mice with Il‐17a ‐knockout mice, we observed that IL‐17a deficiency potentially activated microglia and reduced Aβ deposition in the brain as shown in 9‐month‐old myeloid p38α‐MAPK‐deficient AD mice. Thus, p38α‐MAPK deficiency in all myeloid cells, but not only in microglia, prevents AD progression. IL‐17a‐expressing lymphocytes may partially mediate the pathogenic role of p38α‐MAPK in peripheral myeloid cells. Our study supports p38α‐MAPK as a therapeutic target for AD patients. Abstract : Deficiency of p38α‐MAPK in myeloid cells, but not only in microglia, efficiently attenuates cerebral Aβ and improves cognitive function in APP‐transgenic Alzheimer's disease mice. As possible mechanisms, p38α‐MAPK‐deficient myeloid cells decrease peripheral IL‐17a‐expressing CD4‐positive cells and increase inflammatory activation and Aβ internalization in microglia.